2022
DOI: 10.1186/s13045-021-01223-x
|View full text |Cite
|
Sign up to set email alerts
|

HLF regulates ferroptosis, development and chemoresistance of triple-negative breast cancer by activating tumor cell-macrophage crosstalk

Abstract: Tumor-associated macrophages (TAMs) are major components of the tumor microenvironment (TME) which are closely associated with the tumor malignant progression. However, the regulatory mechanisms by which TAMs influence the progression of triple-negative breast cancer (TNBC) remain unclear. Here, we report that hepatic leukemia factor (HLF) acts as a novel oncoprotein in TNBC. We found that HLF was regulated by transforming growth factor-beta1 (TGF-β1) that is secreted by TAMs. Then, HLF transactivated gamma-gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
79
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(80 citation statements)
references
References 18 publications
1
79
0
Order By: Relevance
“…It is characterized by dysbalance in the regulation of intracellular iron metabolism and membrane lipid peroxidation ( Ursini and Maiorino, 2020 ). The function of ferroptosis in several types of cancer has been reported previously, including breast cancer ( Li H. et al, 2022 ), hepatocellular carcinoma ( Chen et al, 2022 ), gastric cancer ( Zhang et al, 2021 ), head neck squamous cell carcinoma ( Lu et al, 2021 ), lung cancer ( Li and Liu, 2022 ), renal cell carcinoma ( Du et al, 2021 ), ovarian cancer ( Li H.-W. et al, 2022 ), and pancreatic cancer ( Liu et al, 2021 ). Mou et al (2022 ) has found that for LGG the SAT1 activation is closely related to ferroptosis upon ROS induction.…”
Section: Introductionmentioning
confidence: 70%
“…It is characterized by dysbalance in the regulation of intracellular iron metabolism and membrane lipid peroxidation ( Ursini and Maiorino, 2020 ). The function of ferroptosis in several types of cancer has been reported previously, including breast cancer ( Li H. et al, 2022 ), hepatocellular carcinoma ( Chen et al, 2022 ), gastric cancer ( Zhang et al, 2021 ), head neck squamous cell carcinoma ( Lu et al, 2021 ), lung cancer ( Li and Liu, 2022 ), renal cell carcinoma ( Du et al, 2021 ), ovarian cancer ( Li H.-W. et al, 2022 ), and pancreatic cancer ( Liu et al, 2021 ). Mou et al (2022 ) has found that for LGG the SAT1 activation is closely related to ferroptosis upon ROS induction.…”
Section: Introductionmentioning
confidence: 70%
“…Abnormal expression of GGT family proteins, including GGT1, could cause increased oxidative stress within tumor cells, which affects the TIME and influences the response to chemotherapeutic agents. Recently, Li ( 33 ) found that increased expression of GGT1 in triple negative breast cancer caused cisplatin resistance by affecting the hepatic leukemia factor (HLF), a process that may be closely linked to IL-6 levels in the immune microenvironment ( 33 ). In this complex process, GGT1 interacted with components of the immune microenvironment to influence TNBC proliferation, invasion, and platinum resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Once this has occurred, lipid peroxidation reactions are no longer regulated and can proceed up to the fragmentation of phospholipids with consequent derangement of cell membranes – a step catalyzed by the presence of free, redox-active iron. These processes are likely taking place in the experimental model used in the mentioned study ( 7 ), where the protection afforded by GGT1 expression in TNBC against ROS production, lipid peroxidation and cell death is indeed accompanied by increased levels of intracellular GSH.…”
mentioning
confidence: 98%
“…An interesting study has recently described a novel cellular/molecular mechanism leading to CDDP resistance of TNBC, highlighting a crucial role for the expression of gamma-glutamyltransferase 1 (GGT1). An interplay of cancer cells with tumor associated macrophages (TAMs) was in fact described, in which TGF-β1 released by TAMs induces TNBC cells to secrete hepatic leukemia factor (HLF), which in turn transactivates GGT1 ( 7 ). The expression of this enzyme activity is shown to enable resistance to cisplatin by potentiating TNBC defenses against ferroptosis, the peculiar cell death mode consequent to iron-dependent lipid peroxidation.…”
mentioning
confidence: 99%
See 1 more Smart Citation